PENGARUH MEDIA PEMBELAJARAN INTERAKTIF TERHADAP MINAT DAN KEMAMPUAN PEMAHAMAN KONSEP SISTEM EKSKRESI SISWA MTS SWASTA DARUL MUTTAQIN KANDANGAN - Pratiwi, Dian; Hulu, Irwan Lihardo; Huda, Muhammad Komarul (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2024)
This study aims to determine the effect of interactive learning media on the interest and ability to understand the concept of the excretory system of students at MTs Swasta Darul Muttaqin Kandangan in the 2021/2022 Academic Year. The population in this study was all class VIII consisting of 2 classes with a total of 64 students. Sampling was carried out using nonprobability sampling, namely the entire population is a sample. Data analysis was carried out by determining the validity test, reliability test, normality test, homogeneity test and hypothesis test, proven by the